(untitled) (Theatrum historiae, 2015)
The paper focuses on changes in the policy and everyday life practices during the Great War in Pressburg, one of the provincial cities of the Hungarian part of the Austria-Hungary. The strategic geographical location of the city on the state border of Austria and Hungary became problematic during and especially at the end of the war. Regarding the multiethnic character of the city, not only the declaration of loyalty to the state became a problem, but the decision process whether this city will belong to the new state of Czechoslovakia, or to Hungary.